Device profile of the EXALT Model D single-use duodenoscope for endoscopic retrograde cholangiopancreatography: overview of its safety and efficacy. (4th May 2021) - Ehrlich, Dean; Muthusamy, V. Raman
ABSTRACT: Introduction : The management of pancreaticobiliary disorders relies heavily on endoscopic retrograde cholangiopancreatography, which is performed with a duodenoscope. Bacterial colonization of reusable duodenoscopes leading to subsequent infectious outbreaks is well recognized and remains an issue despite efforts to optimize best practices in high-level disinfection. The EXALT Model D duodenoscope (EXALT) (Boston Scientific Corporation, Marlborough, MA) is a single-use device, designed to achieve technical equivalency with reusable devices while eliminating the potential for device-related outbreaks. Areas covered : This review covers the challenges associated with reprocessing duodenoscopes and the development of duodenoscope-related infections, with an emphasis on the use of single-use duodenoscopes as a potential solution to this issue. Expert Opinion : Duodenoscope-related infections are an increasingly recognized problem. Infectious outbreaks harm patients, significantly affect providers and medical centers, and can erode patient trust in the health-care system. Single-use duodenoscopes eliminate both the risk of device-related infection transmission and the need for burdensome duodenoscope reprocessing. In clinical evaluations, the EXALT device has demonstrated an equivalent technical performance and provider satisfaction compared to reusable duodenoscopes. Increasing use of this device will clarify how it compares to reusable duodenoscopes in a variety of clinical settings among endoscopists of varying skills levels.